Case report: meningeal lymphangiogenesis around ependymoma forming along the dura matter - Hino, Utaro; Tamura, Ryota; Yo, Masahiro; Kase, Yoshitaka; Tsuda, Noboru; Miyauchi, Tsubasa; Sogano, Junki; Karatsu, Kosuke; Miwa, Tomoru; Toda, Masahiro (Frontiers in Oncology, 2024)
Recently, there has been growing interest in the presence and function of meningeal lymphatic vessels, with no direct evidence linking these vessels to primary brain tumors. We report a unique case of recurrent ependymoma in the dura mater, showing histopathological signs of lymphatic proliferation at the tumor attachment site. The patient initially presented with a headache, and was diagnosed with ZFTA fusion-positive supratentorial ependymoma, central nervous system WHO Grade 3. Following multiple dura mater recurrences and surgery, the fifth procedure revealed numerous tumors contralateral to the original site, with genetic testing confirming ZFTA fusion positivity, indicating recurrent ependymoma. Immunohistochemical analysis showed D2-40 + lymphatic vessel proliferation around tumor attachment sites within the dura mater. Elevated expression of ZEB1, which is an epithelial-to-mesenchymal transition factor, was also observed, implicating potential involvement in the unique pathophysiology. The present case suggests a new process of metastasis through meningeal lymphatic vessels, although we were unable to visually confirm tumor cell infiltration into the lymphatic vessels. This case is the first report suggesting ependymoma metastasis through dural lymphatic vessels, underlining the need for further case accumulation and study to understand the mechanisms of this phenomenon.